Dithionite and Oxalate Extraction of Iron and Manganese in Some Basement Complex Soils of Southwestern Nigeria - Akinbola, G.E; Adigun, M.O; Aduroja, O (Journal of Experimental Sciences, 2013)
In soil, the presence of free iron oxide serve as important parameters in understanding its development and they are known to influence soil properties. Their influence gives rise to different soil management problems which may inhibit the level of agricultural production. Iron and Manganese were extracted from the basement complex soils of Egbedi area in Osun State, Southwestern-Nigeria. Both Dithionite citrate bicarbonate method and acid ammonium oxalate method were used for the extraction. Dithionite citrate bicarbonate extractant removed both the crystalline and non-crystalline iron and manganese oxides from the soil while the Acid ammonium oxide method removed the non-crystalline or amorphous iron and manganese oxides from the soil. Representative samples were obtained from six (6) well described profile pits. These samples were subjected to analysis for both their physical and chemical properties. Results indicated that soil texture was generally sandy at the surface with increasing proportion of clay with depth. Percentage gravel content showed an irregular trend which indicates the nature of the parent material. The pH values of the soil ranged from 4.7 - 6.4 indicating strong acidity to slight acidity. Magnetite was also dissolved by the Acid ammonium oxalate extractant and this was reflected in the active Fe ratio. Horizons with an active Fe ratio greater than one served as an indicator to the presence of magnetite in such horizons hence values ranging between 1.19 and 4.32 were recorded as active iron ratio in respective horizons. Thus the extraction of iron oxides with Acid ammonium oxalate alongside Dithionite citrate bicarbonate is essential in the differentiation and identification of horizons with magnetite.